Polycyclic aromatic hydrocarbons in samples of Ryugu formed in the interstellar medium - Zeichner, S.S.; Aponte, J.C.; Bhattacharjee, S.; Dong, G.; Hofmann, A.E.; Dworkin, J.P.; Glavin, D.P.; Elsila, J.E.; Graham, H.V.; Naraoka, H.; Takano, Y.; Tachibana, S.; et al. (2023)
Polycyclic aromatic hydrocarbons (PAHs) contain ≲20% of the carbon in the interstellar medium. They are potentially produced in circumstellar environments (at temperatures ≳1000 kelvin), by reactions within cold (~10 kelvin) interstellar clouds, or by processing of carbon-rich dust grains. We report isotopic properties of PAHs extracted from samples of the asteroid Ryugu and the meteorite Murchison. The doubly-13C substituted compositions (D2×13C values) of the PAHs naphthalene, fluoranthene, and pyrene are 9 to 51% higher than values expected for a stochastic distribution of isotopes. The D2×13C values are higher than expected if the PAHs formed in a circumstellar environment, but consistent with formation in the interstellar medium. By contrast, the PAHs phenanthrene and anthracene in Ryugu samples have D2×13C values consistent with formation by higher-temperature reactions.